Noisy neighbours and myna problems: Interaction webs and aggression around tree hollows in urban habitats. Issue 10 (20th July 2020) - Rogers, Andrew M.; Griffin, Andrea S.; van Rensburg, Berndt J.; Kark, Salit
Abstract: Interaction networks among native and invasive species in a community can inform both invasion impacts and applied management of invasive species. The intensity of aggressive interactions may be related to the overlap in species' ecological niche and functional traits, especially in cavity‐breeding species, that often compete for limited nesting sites. Australia is home to over 100 native and introduced cavity‐nesting species, including several invasive species that are widespread globally, such as the common myna Acridotheres tristis . Here, we aimed to test the extent to which shared functional traits inform the intensity of aggression between cavity‐nesting birds. We quantified the outcomes of aggressive interactions between birds in large hollow‐bearing trees in SE Queensland, Australia. We examined whether more similarly sized birds interacted more frequently, whether larger species won aggressive interactions more often, and whether cavity‐breeding species with similar preferences for nesting sites (breeding‐niche space) interacted more frequently. We recorded a total of 410 aggressive interactions and 48 interacting bird species around tree hollows, including 20 cavity‐nesting bird species. These interactions were dominated by the invasive common myna, the native noisy miner (a non‐cavity‐breeder) and the native rainbow lorikeet Trichoglossus moluccanus, but the common myna won the largest total number of interspecific interactions. On average, larger birds won aggressive interactions more frequently, yet there were some important exceptions to this finding; the common myna (113 ± 30 g) won 26 of the 29 interactions against the larger native rainbow lorikeet (126 ± 44 g). Importantly, species with more similar nest‐site preferences were observed aggressively interacting more frequently. Synthesis and applications . The impact of the invasive common myna was higher‐site preferences. Control efforts for the myna should focus on birds that nest in natural tree hollows. An analysis of shared traits by managers could be used to help identify how many local species would benefit from common myna control in a given area and test if further behavioural studies of common myna are warranted. Abstract : The impact of the invasive common myna was higher‐site preferences. Control efforts for the myna should focus on birds that nest in natural tree hollows. An analysis of shared traits by managers could be used to help identify how many local species would benefit from common myna control in a given area and test if further behavioural studies of common myna are warranted.